Clinically Translatable Transcrocetin Delivery Platform for Correction of Tumor Hypoxia and Enhancement of Radiation Therapy Effects (Small 12/2023). Issue 12 (22nd March 2023) - Diringer, Marie‐Charlotte; Coliat, Pierre; Mathieu, Clélia; Laurent, Nina; Mura, Carole; Banerjee, Mainak; Zhu, Chen; Grabowska, Anna; Ritchie, Alison; Clarke, Philip; Bernard, Alexandre; Vit, Claire; et al.
Abstract : Enhancement of Radiation Therapy Effects Liposome‐based nanoparticles encapsulating transcrocetin (NP TSC) act as therapeutic radiosensitizer. In article number 2205961, Alexandre Detappe and co‐workers perform a study on mouse to confirm their ability to reoxygenate triple negative breast cancer tumors for up to 48h. This reoxygenation effect leads to normalisation of the vasculature which enhances the radiation therapy effects.